Teaching and Advocating Green Skills for Students as Social Agents: Sustainability Education Practices of Public-School Teachers at the Secondary Level - Arlene A Zabala; Ryan R Pecson (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The study explores how public secondary teachers teach and advocate green skills for students, highlighting the need for promoting sustainable living and economies in the future. Methodology: Using the descriptive-survey design of quantitative research, eighty-six (86) teachers in public secondary schools in a province in the Philippines are surveyed using a questionnaire with a validity index of 0.98 (excellent) and reliability index of 0.962 (excellent). The gathered data are then analyzed using mean, standard deviation, and t-test. Main Findings: The findings show that public secondary school teachers emphasize immersive, participatory, and interdisciplinary learning when teaching green skills into their classroom practices, revealing the importance of green skills as integral soci-environmental competencies. However, they still need to provide holistic and comprehensive support for developing these skills outside of the classroom. To ensure a more thorough approach to fostering green skills in students, the curriculum can be enhanced to include sustainable development and environmental literacy, and teachers can get professional development to improve their ability to work with organizations and institutions. The study reveals a discrepancy between the actual teaching of green skills and their advocacy, calling for an intensive and sustainable approach to strengthening academic integration as well as sustainable community practice in green education. Novelty/Originality of this study: The study contributes to the body of knowledge by examining the extent to which teaching and advocating green skills can lead to improved teacher professional development initiatives and partnerships for sustainable development, thereby bridging the gap between theoretical frameworks and practices.